(3GSJQGJjLjGJ EOGQI GdehGQO GdHTQjIs - (3SGeM YHO GdeWdH(B, (3YGeQs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2011)
(3eaGgje h CSS h GSJQGJjLjGJ GOGQI GdehGQO GdHTQjI , JUeje GSJQGJjLjGJ JWhjQ GdehGQO GdHTQjI h GSJQGJjLjI GdJMdjd h GdJhUja GdhXjaj , GdGSJbWGH , GdGNJjGQ h GdJYjjf , JWHjb GSJQGJjLjI GdJWhjQ (B:(3GdJOQjH, JWhjQ GdeSGQ GdhXjaj h fXe eYdheGJ, Jbjje COGA GdYGedjf , GdcaGAI GdGfJGLjI h bjGS OhQ GOGQI GdehGQO GdHTQjI , GdOGaYjI h CgOGa GdefXeI , GdGHOGY aj Md GdeTcdGJ h GdJOQjH GdGHOGYj dJMbjb CgOGa GdefXeI , fXe GdCLhQ h GdMhGaR , GOGQI GdJZjjQ h GSJQGJjLjI GdJWhjQ , GOGQI GdeYQaI h GdJWhjQ GdJfXjej (B.s
(3edGMb U(B.341s
Keywords: (3GdGOGQIs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs; (3GdehGQO GdHTQjIs